Lower extremity muscle function of front row rugby union scrummaging - Yaghoubi, M.; Lark, S. D.; Page, W. H.; Fink, P. W.; Shultz, S. P. (Sports Biomechanics, 2019)
A rugby scrum`s front row must act uniformly to transfer maximal horizontal force and improve performance. This study investigated the muscle activation patterns of lower extremity muscles in front row forwards during live and machine scrums at professional and amateur levels. Electromyography was collected bilaterally on vastus lateralis, rectus femoris and gastrocnemius muscles of 75 male rugby prop players during live and machine scrums. ANOVAs compared muscle reaction time, rate of change in muscle amplitude and muscle amplitude between groups and conditions. Cross-correlation analysis explored muscle synchronicity. There were significantly greater rates of change in each muscle amplitude in professional players than amateur players. Additionally, there was significantly quicker muscle reaction time in all muscles, and greater amplitude in vastus lateralis and gastrocnemius, during the live scrum vs. machine condition. The professional props produced more synchronised muscle activation than amateur players and all players produced more synchronised muscle activation against the scrum machine vs. live scrummage. The results indicate a higher skill proficiency and muscle synchronicity in professional players. While scrum machine training is ideally suited for functional muscle strengthening during practice, to truly simulate the requirements of the scrum, training should incorporate the live situation as much as possible.